The relationship between effective listening skills towards employee’s job performance at Jabatan Agama Islam Selangor (JAIS) Shah Alam / Nurul Hazimah Hassan - Hassan, Nurul Hazimah (Faculty of Business And Management, 2014)
Purpose and scope of report: The purposes are to study the relationship between effective listening skills towards job performance and to know the impact of effective listening skills contribute to the employee's job performance. These report also measure what is the most positive impact of effective listening skills can affect the employee's job performance. Methods: These researches describe and explain the sampling plan and the instrument used to generate data and answer. The sampling frame, the sample technique, sample size, unit of analysis, data collection procedures, survey instruments, validity or survey and plan for data analysis are explained in this research. Findings: Described all the findings obtained from the study and discussion of the findings. It consist rate percentage of response, respondent's background and the major discussion of finding based on the research questions developed in this research. There is a significant relationship between effective listening skills and employee's job performance. It was found that there was strong correlation between effective listening skills and employee's job performance (r=.756). Conclusion: The employees at Jabatan Agama Islam Selangor (JAIS) can perceive effective listening skills towards their job performance. Therefore, they need to take an action to increase the job performance. Without good listening skills of employees, effective communication can be distorted. This has negative consequences on job performance and productivity would be negatively affected. Recommendation: The organization can arrange training for interpersonal communication skills which includes how to recognize the barrier to have good listening skills. In that training program, employees can know how to develop active listening skills and how to give and receive feedback. Besides that, employees also can learn how to deal with difficult people.